2004
DOI: 10.1111/j.1399-5618.2004.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with bipolar I depression: data from 920 patients

Abstract: While both unipolar and bipolar depression have serious detrimental effects on patient QOL, our results suggest that some aspects of QOL may be worse in bipolar depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(80 citation statements)
references
References 39 publications
(35 reference statements)
5
67
1
5
Order By: Relevance
“…For many patients with BD, the depressive polarity is often more pervasive and more debilitating than manic states, with estimates that depressed mood accounts for up to two‐thirds of the time spent unwell, even with treatment 12, 223, 224. Subsyndromal depressive symptoms, which persist despite treatment, are particularly common and a major source of functional impairment in these patients 225, 226, 227, 228, 229. They should be treated aggressively.…”
Section: Acute Management Of Bipolar Depressionmentioning
confidence: 99%
“…For many patients with BD, the depressive polarity is often more pervasive and more debilitating than manic states, with estimates that depressed mood accounts for up to two‐thirds of the time spent unwell, even with treatment 12, 223, 224. Subsyndromal depressive symptoms, which persist despite treatment, are particularly common and a major source of functional impairment in these patients 225, 226, 227, 228, 229. They should be treated aggressively.…”
Section: Acute Management Of Bipolar Depressionmentioning
confidence: 99%
“…74, Nineteen studies 74,97,98,[102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117] contained data on the SF-36, one study involved the SF-12 101 and four studies [98][99][100][101] contained data on the EQ-5D. No studies were identified that examined the SF-6D in individuals diagnosed with bipolar disorder.…”
Section: Bipolar Disordermentioning
confidence: 99%
“…BD is associated with a greatly impaired quality of life, increased physical health burden (Vancampfort et al, 2016;Vancampfort et al, 2015) and disability (Hirschfeld et al, 2003;Yatham et al, 2004). Moreover, BD can impact employment (Reed et al, 2010) and lead to lower self-esteem (Nilsson et al, 2010) and reduced social interaction (Judd and Akiskal, 2003).…”
Section: Introductionmentioning
confidence: 99%